Pengembangan Sistem Manajemen Surat Berbasis Web Menggunakan Design Thinking dan Agile-Scrum - An-Nisa Aina Nurwaida; Hendri Julian Pramana; Rio Setiawan; Hazza Rekhsa Faiq Azmahadi; Ahmad Ichsan Mujabar (TIN: Terapan Informatika Nusantara, 2026)
Digital transformation in higher education has increased the demand for more effective, efficient, and integrated correspondence administration systems. However, the Faculty of Communication and Information at Universitas Garut continues to experience problems in managing incoming and outgoing correspondence because letter numbering, document distribution, disposition, and archiving processes are still performed manually and are not yet integrated. These conditions result in administrative delays, an increased risk of recording errors and data duplication, difficulties in retrieving archived documents, and reduced efficiency of administrative services. This study aims to develop a web-based Mail Management System by applying the Design Thinking approach to User Interface (UI) and User Experience (UX) design while adopting the Agile-Scrum framework as an iterative and adaptive software development methodology. The research stages consisted of user needs identification, prototype design, system development, feature implementation, and usability evaluation using the System Usability Scale (SUS). The developed system provides integrated features, including automated letter numbering, incoming and outgoing mail management, user and access management, letter templates, period and organizational unit management, letter disposition, and digital archiving. The usability evaluation involving six respondents produced an average SUS score of 70, which falls into the Acceptable category with a Grade C, indicating that the system has good usability and is acceptable to users. The findings of this study indicate that the integration of Design Thinking and Agile-Scrum is an effective approach for developing a web-based Mail Management System that is aligned with user needs.